2017
DOI: 10.1111/epi.13692
|View full text |Cite
|
Sign up to set email alerts
|

Adult motor phenotype differentiates Dravet syndrome from Lennox‐Gastaut syndrome and links SCN1A to early onset parkinsonian features

Abstract: Distinguishing adult patients with Lennox-Gastaut syndrome from those with Dravet syndrome is challenging. We have previously reported that patients with Dravet syndrome present a very peculiar motor phenotype. Here we sought to confirm that this association was not linked to the chronic use of antiepileptic drugs or the many lifetime seizures. To this aim, we studied 14 adult patients with Lennox-Gastaut syndrome and 14 adults with Dravet syndrome because both conditions share similar seizure severity. We fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 13 publications
(29 reference statements)
2
44
0
Order By: Relevance
“…Long-term AED use and the seizures themselves are often blamed for the negative issues that patients experience. This study, which found 75% of patients experience gait disturbances, supports the recent finding that gait issues are a unique characteristic of DS, even when compared with Lennox-Gastaut syndrome, whose patients share a long history of multiple AED use and frequent seizures [16]. Certain conditions that appear age-related in this survey such as osteopenia and broken bones may indeed be the result of long-term medication use and are common in the general population with epilepsy [17].…”
Section: Dravet Syndrome Vs Epilepsy In Generalsupporting
confidence: 86%
“…Long-term AED use and the seizures themselves are often blamed for the negative issues that patients experience. This study, which found 75% of patients experience gait disturbances, supports the recent finding that gait issues are a unique characteristic of DS, even when compared with Lennox-Gastaut syndrome, whose patients share a long history of multiple AED use and frequent seizures [16]. Certain conditions that appear age-related in this survey such as osteopenia and broken bones may indeed be the result of long-term medication use and are common in the general population with epilepsy [17].…”
Section: Dravet Syndrome Vs Epilepsy In Generalsupporting
confidence: 86%
“…For example, ataxia and crouching gait seen in Dravet syndrome may be related to SCN1A mutations, 17 whereas spastic paralysis, seen in a small number of patients with Dravet syndrome, may be the sequelae of acute encephalopathy caused by status epilepticus. [18][19][20] Our analysis of patients in the lowest and highest seizure strata also did not reveal a significant difference between the two groups for autism, ADHD, and other behavioural problems. These discrepancies indicate that seizure frequency is not the only factor to explain comorbidities, as already shown in other smaller studies.…”
Section: Discussionmentioning
confidence: 47%
“…We speculate that this earlier developmental window may reduce the vulnerability of primary and sensory systems to potential impacts of LGS on thalamocortical maturation. Consistent with this hypothesis, some patients with LGS show a relative preservation of motor functions compared to patients with other epileptic encephalopathies . Additionally, abnormal metabolism on FDG‐PET typically spares primary cortex in LGS, and ictal SPECT and interictal EEG‐fMRI studies show reduced involvement of primary cortical areas during epileptic activity.…”
Section: Discussionmentioning
confidence: 66%
“…Consistent with this hypothesis, some patients with LGS show a relative preservation of motor functions compared to patients with other epileptic encephalopathies. 40 Additionally, abnormal metabolism on FDG-PET typically spares primary cortex in LGS, 2 and ictal SPECT 6 and interictal EEG-fMRI 3-5 studies show reduced involvement of primary cortical areas during epileptic activity.…”
Section: Discussionmentioning
confidence: 99%